2001
DOI: 10.3354/dao045061
|View full text |Cite
|
Sign up to set email alerts
|

Induction of proliferative kidney disease (PKD) in rainbow trout Oncorhynchus mykiss via the bryozoan Fredericella sultana infected with Tetracapsula bryosalmonae

Abstract: Proliferative kidney disease (PKD) is a serious infection of wild and farmed salmonids, affecting mainly the kidney and spleen but becoming systemic in most susceptible fish hosts. This report deals with the transmission of Tetracapsula bryosalmonae Canning, Curry, Feist, Longshaw & Okamura 1999 from naturally infected bryozoans Fredericella sultana Blumenbach 1779 to naïve rainbow trout Oncorhynchus mykiss Walbaum 1792, thereby confirming the recent conclusion based on partial 18S rDNA sequence data that bryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 23 publications
3
103
0
Order By: Relevance
“…data). Furthermore, Feist et al (2001) obtained transmission of T. bryosalmonae by cohabitation of fish with infected bryozoan material in a flowthrough system where the continuous loss of spores should have resulted in low concentration. Hedrick et al (2004) estimated a maximum concentration of 120 T. bryosalmonae spores ml -1 fish urine, thus spores should become highly dilute upon release from fish in natural populations.…”
Section: Constraints Of Studymentioning
confidence: 99%
“…data). Furthermore, Feist et al (2001) obtained transmission of T. bryosalmonae by cohabitation of fish with infected bryozoan material in a flowthrough system where the continuous loss of spores should have resulted in low concentration. Hedrick et al (2004) estimated a maximum concentration of 120 T. bryosalmonae spores ml -1 fish urine, thus spores should become highly dilute upon release from fish in natural populations.…”
Section: Constraints Of Studymentioning
confidence: 99%
“…The parasite life-cycle, as currently understood, includes bryozoans as invertebrate hosts (Anderson et al 1999, Longshaw et al 1999, Okamura et al 2001 and salmonids as vertebrate hosts (Feist & Bucke 1993, Hedrick et al 1993. T. bryosalmonae infects fish through skin and gills (Feist et al 2001, Longshaw et al 2002 and after invasion is distributed systemically via the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…The parasite life-cycle, as currently understood, includes bryozoans as invertebrate hosts (Anderson et al 1999, Longshaw et al 1999, Okamura et al 2001 and salmonids as vertebrate hosts (Feist & Bucke 1993, Hedrick et al 1993. T. bryosalmonae infects fish through skin and gills (Feist et al 2001, Longshaw et al 2002 and after invasion is distributed systemically via the blood stream. The main target organ is the kidney (Kent & Hedrick 1985) where T. bryosalmonae undergoes multiplication and differentiation from extrasporogonic to sporogonic stages (Kent & Hedrick 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission experiments have recently established that T. bryosalmonae is the enigmatic PKX organism, which causes the economically important disease of salmonids, proliferative kidney disease, PKD (Feist et al 2001). Phylogenetic studies on T. bryosalmonae and T. bryozoides demonstrated that both parasites formed a distinct clade within the Myxozoa (Kent et al 1998, Anderson et al 1999.…”
mentioning
confidence: 99%